2021
DOI: 10.3386/w28354
|View full text |Cite
|
Sign up to set email alerts
|

Hit Harder, Recover Slower? Unequal Employment Effects of the Covid-19 Shock

Abstract: The destructive economic impact of the Covid-19 pandemic was distributed unequally across the population. Gender, race and ethnicity, age, education level, and a worker's industry and occupation all mattered. We analyze the initial negative effect and the lingering effect through the recovery phase across demographic and socio-economic groups. The initial negative impact on employment was larger for women, minorities, the less educated, and the young, even after accounting for the industries and occupations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 10 publications
2
42
0
Order By: Relevance
“…Unemployed workers with jobs returned to employment much faster than "jobless" unemployed workers who had no job to return to. Bick and Blandin (2020), Cajner et al (2020) and Lee et al (2021) provide further evidence on the importance of recall unemployment in 2020.…”
Section: Introductionmentioning
confidence: 81%
“…Unemployed workers with jobs returned to employment much faster than "jobless" unemployed workers who had no job to return to. Bick and Blandin (2020), Cajner et al (2020) and Lee et al (2021) provide further evidence on the importance of recall unemployment in 2020.…”
Section: Introductionmentioning
confidence: 81%
“…Examples of the concerns raised by this pandemic include whether initial supply shocks can lead to deficits in demand (Brinca et al [13]), how the magnitudes of supply and demand shocks compare across industries (Guerrieri et al [14]), and what socioeconomic implications of a global pandemic might persist in the future (Nicola et al [15]). Other research focused on the impact to employment caused by the health crisis; Lee et al [16] analyzed the impact on employment rates and their subsequent recoveries across demographics, Blustein et al [17] presented avenues for research on strategies for dealing with the large unemployment rates, and identifying vulnerable workers, Milani [18] found that the response in unemployment varied across countries and that the U.S. employment rate was particularly susceptible to health shocks, and Farrell et al [19] investigated the relationship between unemployment insurance and aggregate consumption. Barrot et al [20] used a general equilibrium model with Cobb-Douglas technologies to determine the economic impact of social distancing and the resulting labor reduction in France, Carvalho and Tahbaz-Salehi [21] presented a literature review of these production network models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These actions, together with voluntary social distancing, appear to have reduced the rates of new COVID-19 cases, deaths, 2 and hospitalizations 3 but were also associated with substantial increases in unemployment and other economic hardships. [4][5][6] To alleviate financial harms, several states started reopening at the end of April 2020. By the middle of May 2020, most nonessential businesses had resumed at least some activities nationwide.…”
Section: Introductionmentioning
confidence: 99%